Accounting Harmonization Measurement: The Case of Non-Banking Financial Institutions in Romania - Denis Levanti; Ileana Cosmina Pitulice; Aurelia Stefanescu (Journal of Accounting and Management Information Systems (JAMIS), 2021)
Research Question - What is the degree of formal harmonization between IFRS and the national accounting framework currently applied by the non-banking financial institutions (NBFI) in Romania? Motivation - Measuring the degree of formal accounting harmonization is beneficial in the context of the first-time adoption of IFRS by NBFI in Romania (2019 – 2022 for information purposes and starting with 2023 as basis for accounting). Despite the popularity of the accounting harmonization topic at the level of international literature, few studies envisage the particular cases of emerging countries, and especially of institutions operating in the financial services sector (banking and non-banking). Idea - The objective of this paper is to evaluate the degree of harmonization between IFRS and the Romanian accounting framework currently applied by NBFI. Dissimilarities between the accounting policies under the two GAAPs are described and discussed. Data - Sample for review consists of 38 accounting topics, selected from: IAS 1 "Presentation of financial statements", IFRS 1 "First time adoption of IFRS", IFRS 9 "Financial instruments", IFRS 16 "Leases" and IAS 12 "Income taxes". Tools - Jaccard's similarity coefficient was used to measure the formal harmonization between IFRS and the Romanian accounting framework applicable to NBFI. Findings - Based on the analyses conducted, a 38.89% similarity coefficient was determined. The areas where the accounting principles are the most compatible relate to the presentation of financial statements and the accounting by lessors. The most significant dissimilarities relate to the accounting principles for the classification, measurement and impairment of financial assets. Contribution - Enrichment of the literature in the field of formal accounting harmonization, as well as of the studies focused on institutions operating in the financial services sector, their number being currently limited. The results obtained provide valuable insights to both, representatives of the academic environment, as well as professionals within NBFI, with regards to the main differences between IFRS principles and the national accounting framework currently applied and specific adjustments to be performed when preparing the first set of IFRS financial statements.
Keywords: M41; 650; IFRS; convergence; harmonization; non-banking financial institution